CRYSTALLINE PHASE REACTIVITY IN THE SYNTHESIS OF FLY ASH-BASED GEOPOLYMER - Lukman Atmaja; Hamzah Fansuri; Anggaria Maharani (Indonesian Journal of Chemistry, 2011)
Aluminosilicate, alkaline solution and fly ash from a power plant have been used to synthesize geopolymer at ambient temperature. SiO2/Al2O3 mole ratio of the starting materials was varied by the addition of pure, insoluble corundum and quartz. The geopolymer exhibited some differences in the ratio of initial reaction mixtures and that of final products. The corundum gave no influence to the compressive strength while the quartz at SiO2/Al2O3=4.0-6.0 produced significant change in the strength. The highest compressive strength achieved was 65 MPa. XRD using analysis Rietveld method proved that quartz has been found both in starting materials as well as in the geopolymer indicating the involvement of crystalline phases, to some extent, in geopolymerization process.